Critical mass : printmaking beyond the edge - Noyce, Richard (London : A. and C. Black, 2010)
The work in this volume describes mediums used in a range from new variations on traditional intaglio and relief techniques to extreme forms of digital techniques, including time-based forms such as film and multi-media presentation. The book provides a broad-ranging and challenging source of information on cutting edge developments in international printmaking.--Publisher
Includes bibliographical references and index
Keywords: Prints -- Technique